ANALISIS PELAKSANAAN AKAD PEMBIAYAAN MURABAHAH PADA BPRS HAJI MISKIN PANDAI SIKEK - Rifqul ‘Afif; Choirul Umam (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
This study aims to determine the implementation of the murabahah contract at the BPRS Haji poor Pandai Sikek. And to determine the management of murabahah financing at the BPRS Haji poor Pandai Sikek. The type of research carried out is field research, which is one method of collecting data with a qualitative research approach, namely research aimed at describing and analyzing phenomena of events, social activities, attitudes, beliefs, perceptions, thoughts of people in general. individually or in groups. Based on the results of the study, it shows that to see that murabahah financing is in accordance with sharia or cannot be seen from the scheme and the flow must be in accordance with the existing pillars and contracts and the murabahah financing process at the Haji Poor Pandai Sikek BPRS is in accordance with the FATWA DSN-MUI No. 4 of 2000 regarding murabaha financing.